Systematic inspection on the interplay between MoNa-induced sodium and the formation of MoSe2 intermediate layer in CIGSe/Mo heterostructures - Za?abar F.?.; Doroody C.; Soudagar M.E.M.; Chelvanathan P.; Abdullah W.S.W.; Zuhd A.W.M.; Cuce E.; Saboor S. (Springer, 2025)
The critical impact of sodium-doped molybdenum (MoNa) in shaping the MoSe2 interfacial layer, influencing the electrical properties of CIGSe/Mo heterostructures, and achieving optimal MoSe2 formation conditions, leading to improved hetero-contact quality. Notably, samples with a 600-nm-thick MoNa layer demonstrate the highest resistivity (73 ?cm) and sheet resistance (0.45 /square), highlighting the substantial impact of MoNa layer thickness on electrical conductivity. Controlled sodium diffusion through MoNa layers is essential for achieving desirable electrical characteristics, influencing Na diffusion rates, grain sizes, and overall morphology, as elucidated by EDX and FESEM analyses. Additionally, XRD results provide insights into the spontaneous peeling-off phenomenon, with the sample featuring a ~ 600-nm MoNa layer displaying the strongest diffraction peak and the largest crystal size, indicative of enhanced Mo to MoSe2 conversion facilitated by sodium presence. Raman spectra further confirm the presence of MoSe2, with its thickness correlating with MoNa layer thickness. The observed increase in resistance and decrease in conductivity with rising MoSe2 layer thickness underscore the critical importance of optimal MoSe2 formation for transitioning from Schottky to ohmic contact in CIGSe/Mo heterostructures. Ultimately, significant factors to the advancement of CIGSe thin-film solar cell production are discussed, providing nuanced insights into the interplay of MoNa and MoSe2, elucidating their collective impact on the electrical characteristics of CIGSe/Mo heterostructures. Graphical Abstract: (Figure presented.). ? The Author(s) 2024.